E-selectin inhibition with GMI-1271 decreases venous thrombosis without profoundly affecting tail vein bleeding in a mouse model - Culmer, Dorian L.; Dunbar, Misha L.; Hawley, Angela E.; Sood, Suman; Sigler, Robert E.; Henke, Peter K.; Wakefield, Thomas W.; Magnani, John L.; Myers, Daniel D., Jr. (Thrombosis and Haemostasis, 2017)
Selectins, such as E-selectin (CD62E), function in venous thrombosis by binding and activating immune cells to initiate the coagulation cascade. GMI-1271 is a small molecule antagonist that inhibits E-selectin activity. Here we determine whether inhibition of E-selectin is sufficient to decrease acute venous thrombosis and associated inflammatory events in both prophylactic and treatment protocols without significantly affecting haemostasis. Male C57BL/6 mice underwent surgery for experimental thrombosis induction and were harvested at peak thrombus formation in our animal model, two days post induction. Groups included non-thrombosed true controls, shams, controls, and prophylactic or treatment groups of GMI-1271 (10 mg/kg intraperitoneal BID (twice a day) and low-molecular-weight heparin (LMWH, Lovenox 6 mg/kg subcutaneously (SC), once a day (SID). Compared with control animals, prophylaxis or treatment with LMWH and GMI-1271 in a dose-dependent manner significantly decreased thrombosis. GMI-1271 significantly lowered tail bleeding times when compared to LMWH. GMI-1271 and LMWH prophylactically administered significantly decreased vein wall neutrophil cell extravasation. However, all treatment and prophylactic therapies significantly decreased vein wall monocyte extravasation versus controls. GMI-1271 prophylactic therapy significantly decreased intra-thrombus cell counts versus control animals and other treatment groups. Immunohistochemistry confirmed that both treatments with GMI-1271 and LMWH significantly decreased activated leukocyte migration. GMI-1271 therapy significantly decreased thrombus weight and resulted in significantly lower bleeding times than LMWH. GMI-1271 treated mice showed decreased local and systemic inflammatory effects while modulating neutrophil activation, suggesting that GMI-1271 is a viable therapeutic candidate for venous thrombosis prophylaxis and treatment.
Keywords: E-selectin inhibition; glycomimetic; venous thrombosis; animal models; inflammation